2000
DOI: 10.1021/bi0008938
|View full text |Cite
|
Sign up to set email alerts
|

DNA Helicase RepA:  Cooperative ATPase Activity and Binding of Nucleotides

Abstract: The steady-state kinetic parameters of the ATPase activity of the homohexameric DNA helicase RepA and the binding of the fluorescent analogue epsilonADP to RepA have been studied. ssDNA stimulates RepA ATPase activity optimally at acidic pH 5.3-6.0. The sigmoidal kinetic curves in both the absence and presence of ssDNA show strong positive cooperativity for ATP hydrolysis, with oligonucleotides longer than 10mer optimal for ssDNA-stimulated ATPase activity. Fluorescence titrations show that, at 25 degrees C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…An open and a more closed conformation are arranged in alternating positions in the cubic structure of RepA, demonstrating the existence of three equivalent dimers in the hexameric ring structure associated with two types of ATP binding sites. This ®nding is also in agreement with biochemical studies which showed that the ATP binding sites in RepA are not identical but three are of low and three of high af®nity for ATP (34). Mechanistically this is probably important because the conversion of the open into the closed type adenine binding site may lead to some kind of a pulsation of the molecule that could periodically change the diameter or the shape of the central hole.…”
Section: Mechanistic Implications Of the Two Conformations Observed At The Subunit Interfacessupporting
confidence: 88%
“…An open and a more closed conformation are arranged in alternating positions in the cubic structure of RepA, demonstrating the existence of three equivalent dimers in the hexameric ring structure associated with two types of ATP binding sites. This ®nding is also in agreement with biochemical studies which showed that the ATP binding sites in RepA are not identical but three are of low and three of high af®nity for ATP (34). Mechanistically this is probably important because the conversion of the open into the closed type adenine binding site may lead to some kind of a pulsation of the molecule that could periodically change the diameter or the shape of the central hole.…”
Section: Mechanistic Implications Of the Two Conformations Observed At The Subunit Interfacessupporting
confidence: 88%
“…The RepA protein is a hexameric DNA replicative helicase that is essential for replication of the RFS1010 plasmid, a broad host nonconjugative plasmid that can replicate in most Gram-negative bacteria and confers bacterial resistance to sulfonamides and streptomycin (accompanying paper 1,[1][2][3][4][5][6][7][8]. The protein forms a very stable, ring-like hexameric structure in the absence of any cofactors or salt in solution (3,5,6).…”
mentioning
confidence: 99%
“…For rotating motors, their channel diameter should be no larger than 2 nm (the diameter of a dsDNA) to allow for close contact between a DNA and the channel wall for threading, since a ssDNA within the channel displays an A form helical structure and is smaller than 2 nm in diameter . Examples include rotating motors of DnaB, Rho factor, TrwB, MCM, and RepA or RuvB, all of which have a channel diameter of 1–2 nm …”
Section: Revolving and Rotating Motors Can Be Distinguished By Their ...mentioning
confidence: 99%
“…Revolving rather than rotating avoids the coiling and tangling of long polymer chains, such as genomic dsDNAs during translocation. The well-studied rotating motors include F1/F0 ATPase, DNA helicase, , Rho transcription termination factor, TrwB, MCM, , and RepA or RuvB, all of which have a channel diameter of 1–2 nm . Revolving motors include the DNA translocases Ftsk in Gram-negative bacteria, SpoIIIE or SftA (YtpS) in Gram-positive bacteria, A32 ATPase of poxvirus, DNA packaging enzyme of adenovirus, the genome segregation enzymes of mimivirus, , as well as the DNA packaging motors of herpesvirus, SPP1, T7, HK97, P22, and Phi29 .…”
mentioning
confidence: 99%